Identificação de bolhas em ações de bancos comerciais do mercado de capitais brasileiro - Silveira, Rubem Garcia da (Universidade Federal de São Carlos, 2023)
The actions of speculators can generate divergences between the market price of an asset and its fundamental price, creating speculative bubbles. This study aimed to verify whether the actions of the four largest commercial banks traded on the Brazilian stock exchange are less susceptible to price exuberance than stocks from different sectors in the same market. To date possible periods of bubbles in the selected stocks, the Generalized Supremum Augmented Dickey-Fuller (GSADF) right-tailed test model was adopted with the addition of a Wild Bootstrap process, as indicated by Phillips and Shi (2020). Based on the found results, and on international literature about the subject, it was verified that the chosen banking stocks are more resistant to price exuberance than stocks from other sectors of the Brazilian economy. At the 5% confidence interval, no bubble event was detected for banking stocks, while some cases were found for the remaining sectors stocks. In order to further test this resistance, a test with a 10% confidence interval was also adopted, where some bubble events were found for both types of stocks. The conclusion of this study is useful for investors that operate in the Brazilian stock market, as well as for stakeholders of the analyzed banks, since they can use this information to better position themselves in the market and build more appropriate portfolios, reducing their exposure to speculative risks.
Identification of bubbles in stocks of commercial banks of the brazilian capital market
Keywords: Mercado Bancário; Bolhas Especulativas; Modelo GSADF; Bolsa de Valores; Wild Bootstrap; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::INSTITUICOES MONETARIAS E FINANCEIRAS DO BRASIL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::TEORIA MONETARIA E FINANCEIRA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::TEORIA ECONOMICA